1999
DOI: 10.1097/00001756-199907130-00008
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homocysteine and the methylenetetrahydrofolate reductase C677T gene variant

Abstract: Disturbances in methyl-carbon metabolism, which result in hyperhomocysteinemia, have been associated with schizophrenia. Homozygosity for the T677 allele of the methylenetetrahydrofolate reductase (MTHFR) gene, which encodes for a thermolabile enzyme associated with hyperhomocysteinemia, has been found to be increased in schizophrenic patients. We have investigated whether plasma homocysteine concentration and the frequency of C677T MTHFR variant were increased in schizophrenic inpatients of a psychiatric hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 1 publication
2
43
1
Order By: Relevance
“…Data for the meta-analysis were obtained from eight published case-control studies 22,[29][30][31][32][33][34][35] with a total number of 812 cases and 2113 control subjects. Figure 1 shows the ORs and 95% CIs of schizophrenia associated with a 5 mmol/l increase in measured plasma total homocysteine, separately for individual studies and for all studies when taken together.…”
Section: Homocysteine and Schizophreniamentioning
confidence: 99%
See 3 more Smart Citations
“…Data for the meta-analysis were obtained from eight published case-control studies 22,[29][30][31][32][33][34][35] with a total number of 812 cases and 2113 control subjects. Figure 1 shows the ORs and 95% CIs of schizophrenia associated with a 5 mmol/l increase in measured plasma total homocysteine, separately for individual studies and for all studies when taken together.…”
Section: Homocysteine and Schizophreniamentioning
confidence: 99%
“…A total of nine published articles 22,31,33,[36][37][38][39][40][41] reported on the relationship between schizophrenia and the MTHFR 677C4T polymorphism. One article provided data on two separate studies.…”
Section: Mthfr and Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations
“…Later on, one study had showed that 45% of the patients of schizophrenia had higher homocysteine concentration [42]. However, Virgos et al [43] reported contradictory findings and showed that the blood homocysteine concentration was not significantly different between schizophrenia patients and normal subjects. According to previous studies, though results are not consistent, it can be assumed that hyperhomocysteinemia may be correlated to schizophrenia like psychosis to some extent.…”
Section: Discussionmentioning
confidence: 99%